A cohort study of relationship between serum calcium levels and cerebral microbleeds (CMBs) in ischemic stroke patients with AF and/or RHD. Issue 26 (June 2016) - Liu, Junfeng; Wang, Deren; Xiong, Yao; Liu, Bian; Wei, Chenchen; Ma, Zhenxing; Wu, Bo; Yuan, Ruozhen; Tang, Hehan; Liu, Ming
Abstract : Abstract: Calcium is an essential element for life and has cerebroprotective property in stroke patients. Low serum calcium levels were found to be related to large hematoma volumes in intracerebral hemorrhagic patients and hemorrhagic transformation in ischemic stroke patients after thrombolysis. However, their impact on hemorrhage-prone small vessel disease represented by cerebral microbleeds (CMBs) is uncertain. We aim to investigate whether low serum calcium levels are associated with presence and location of CMBs. Ischemic stroke patients with atrial fibrillation (AF) and/or rheumatic heart disease admitted to our hospital were consecutively and prospectively enrolled. Demographic and clinical information were collected and analyzed according to the occurrence and location of CMBs, and levels of serum calcium. We used logistic regression analysis to estimate the multivariable adjusted relationship between serum calcium levels and the presence or location of CMBs. Among the 67 patients (28 males; mean age, 67.3 years) in the final analysis, 39 (58.2%) were found to have CMBs. After adjustment for age, sex, smoking habits, drinking habits, and renal impairment, the presence of CMBs and deep CMBs was, respectively, 4.96- and 4.83-fold higher in patients with lower serum calcium levels (⩽2.15 mmol/L) than in patients with higher serum calcium levels. Lower serum calcium levels (⩽2.15 mmol/L) are independently associated with the presence of CMBs and deep CMBs in ischemic stroke patients with AF and/or rheumatic heart disease, which should be verified and extended in large cohorts, with other types of stroke patients and the general population.